A Diazaborine-Based ROS Switch Enables Copper Transfer for Tumor-Specific Prodrug Activation and Therapy - Zeqian Huang; Yaqing Ding; Shengzhi Wang; Zijun Lin; Conghan Wang; Dong Zheng; Tao Zhang; Chunshun Zhao (Molecular Pharmaceutics, 2026)
Abstract Reactive oxygen species (ROS) are significantly elevated in tumor cells, providing an intrinsic trigger for selective drug activation and tumor-specific therapy. However, commonly used ROS-responsive linkers, such as thioketals and boronates, often suffer from limited sensitivity or poor physiological stability, and the development of new ROS-responsive motifs remains scarce. Herein, we develop a hydrazide-derived diazaborine (DAB) scaffold and establish it as a general ROS-responsive linker for small-molecule prodrugs, combining physiological stability with efficient ROS responsiveness. Based on this platform, we construct a DAB-derived ROS-responsive copper complex small-molecule prodrug, DDABD@Cu, for tumor-specific therapy. DDABD@Cu integrates a DAB-caged diethyldithiocarbamate (DTC) moiety with an inert copper donor, in which the DAB group effectively blocks the copper-chelating activity of DTC, enabling inert co-delivery of both components. Upon ROS activation, DTC is released to initiate copper transfer, generating cytotoxic Cu(DTC)2 in situ to induce proteotoxic stress via ubiquitinated protein accumulation while concomitantly producing quinone methide (QM) to deplete glutathione (GSH) and amplify oxidative stress. This cascade improves antitumor efficacy against non-small cell lung cancer while limiting off-target toxicity. Overall, this work provides a feasible strategy for designing ROS-responsive and copper complex prodrugs.